Organization and metrics of the Division of Advanced Cardiac Imaging, King Abdulaziz Cardiac Center. (November 2014) - Al-Mallah, Mouaz H.; Aljizeeri, Ahmed; Suliman, Ihab; Alharthi, Mohsen; Alhabshan, Fahad; Alsaileek, Ahmed
Abstract: Non-invasive cardiac imaging (including nuclear cardiology, cardiac computed tomography, and cardiac magnetic resonance imaging) developed rapidly over the past few years. The leadership of King Abdulaziz Cardiac Center (KACC) adopted the concept of multimodality imaging cardiologist and developed in the year 2000 a strategic plan to invest in this new branch of cardiology. A new cardiac imaging center is currently under construction with the aim to be the hub for large enterprise of clinical, research, and educational activities. Awaiting the completion of the new imaging center, the division has been active in supporting a busy clinical service in temporary locations that allow access to all imaging modalities. Of note, the first 82-Rubidium cardiac PET MPI in the Middle East was performed at KACC in 2011. In addition, the imaging division plays an important role in the teaching and training of medical and paramedical students as well as community cardiologists and radiologist instructing them on the best practices in advanced cardiac imaging. Moreover, research is going to be an integral part of the division mission with >10 research protocols currently being active in the division. Thus, the advanced cardiac imaging division at KACC performs high-quality clinical work, educates and teaches local and regional physicians, and performs research. In short, it is a Saudi cardiac imaging service that operates on high-quality academic standards.